Field study 1 : the learner's development and environment - Salana, June P. (Manila, Philippines : Rex Book Store, 2013)
This book is designed to help the Field Study students verify the behaviour of the child in the actual learning environment.
Students' expected outcomes 1 -- Field experience 2 -- Field studies and applied curriculum tasks 4 -- Activity -- Social dimension of education 31 -- Activity -- Read! Multiple metaphors for learning 45 -- Activity -- Theories on individual differences 59 -- Defining learning styles 59 -- Cognition: how do I know 59 -- Activity -- References 64 -- Online sources 65
Includes bibliographical references.
Keywords: EDUCATION -- PHILIPPINES